In Vitro Evaluation of Antibacterial Potential BioMint D-Spray Derived from Anredera cordifolia and Mentha spicata Extracts on Diabetic Wound Pathogens - Maulida, Mas'ulatur Rohmah; Ardani, Nandita Diva; Putri , Anggi Ananta; Kuswidyaningrum, Desviona; Museyaroh (Ahmad Dahlan Medical Journal, 2026)
Diabetes mellitus is a metabolic disorder associated with a high risk of complications, particularly Diabetic Foot Ulcers (DFU). Indonesia recorded approximately 20.4 million diabetes cases in 2024, increasing the demand for effective and affordable wound care. Anredera cordifolia and Mentha spicata contain bioactive compounds including flavonoids, saponins, carvone, and phenolic acids with proven antibacterial and anti-inflammatory properties, making them promising natural candidates for diabetic wound management. This study employed a true experimental design using a combined extract of Anredera cordifolia and Mentha spicata leaves at a 1:1 ratio prepared via maceration. Phytochemical screening and pH testing were performed to characterize the extract. Antibacterial activity was assessed using the well diffusion method at concentrations of 60%, 70%, 80%, 90%, and 100%, followed by incubation for 12 and 24 hours and observed. Inhibition zone diameters were analyzed using the Shapiro-Wilk normality test followed by One-Way ANOVA at α = 0.05. Phytochemical analysis confirmed the presence of flavonoids, alkaloids, and tannins, with all concentrations exhibiting an acidic pH of 4.0. Antibacterial activity against Staphylococcus aureus was observed across all concentrations, with 60% established as the minimum inhibitory concentration (MIC). Inhibition zone diameters ranged from 14.20 mm to 15.40 mm across observation periods. The combined extract demonstrated intermediate antibacterial activity against Staphylococcus aureus based on CLSI standards, with inhibition zones of 14.20 to 15.40 mm compared to novobiocin (22 mm). No statistically significant difference was observed between concentrations. Further in vivo studies are recommended to evaluate pharmacological effects and optimal concentration in biological systems.